Impact Analysis of Web Application Firewall on Website-Based Application Security (Case Study PPDB Kak Seto School Website) - Pratama, Krisna Dewa; Anwar, Nuril (Universitas Ahmad Dahlan, 2023)
The swift advancement of web-based applications has posed security challenges. Insufficient security awareness among web developers has resulted in a surge of cybercrime incidents due to website vulnerabilities. To counter this, implementing a Web Application Firewall (WAF) is proposed for the vulnerable PPDB Sekolah Kak Seto website, aiming to mitigate threats in the public network. The WAF acts as a defense against potential cyber breaches. Employing an experimental approach, this research encompasses identification, observation, literature review, analysis of WAF system requirements, implementation, testing, and pre/post-implementation analysis using ModSecurity as the security system. The study analyzes the impact of WAF adoption and provides recommendations for enhancing security. Findings demonstrate WAF's effectiveness in fortifying the Kak Seto School web application by efficiently identifying and blocking potential attacks, thereby reducing breach success rates. Post-WAF implementation, Pingdom tests show a slight drop in Performance Grade (70 to 69) and a minor increase in Load Time (2.76 to 3.23 seconds). GTmetrix tests reveal a Grade downgrade from B to C and an increase in Largest Contentful Paint time (2.2 to 2.7 seconds). In conclusion, despite minor performance effects, WAF significantly enhances security, as evident in improved loading times during tests.